Internalisasi Nilai-Nilai Pendidikan Agama Islam Melalui Bina Pribadi Islami (BPI) Dalam Pencegahan Prilaku Bullying Siswa SMPIT dan SMAIT Insan Cita Serang: Islamic Religious Education Values, Preventing Bullying - Tb ahmad Munada; Ilzamudin Mamur; Lalu Tujiman; Wasehudin (Mu'allim, 2025)
Internalizing Islamic religious values is the process of fully incorporating religious values into the heart, so that the spirit and soul move according to Islamic teachings. One method that can be used to internalize Islamic values is through the Islamic Personal Development program, because through this activity, students can apply the instilled Islamic values in their daily lives. This study aims to analyze the implementation of the Islamic Personal Development (BPI) program in internalizing Islamic religious education values and its impact on preventing bullying behavior at Insan Cita Serang Junior High School (SMPIT) and Senior High School (SMAIT). Based on the research problem formulation, this study examines the implementation of the BPI program, the internalized Islamic religious values, the program's implications for bullying, and the supporting and inhibiting factors that influence student bullying behavior. The method used was a qualitative approach through interviews and observations with the principal, Islamic Personal Development instructors, Islamic Education teachers, Guidance and Counseling teachers, and students. The results of the study indicate that the BPI program is effective in internalizing Islamic values, such as honesty, empathy, compassion, and responsibility, which are applied in students' daily lives. The positive impact is seen in a significant decrease in bullying cases, with a more harmonious and respectful school atmosphere. Supporting factors such as school commitment and cooperation with parents strengthen implementation, while limited facilities and infrastructure are obstacles. This study concludes that the Bina Pribadi Islami program plays a significant role in preventing bullying and developing positive character in students. This program needs to be strengthened and continued to optimize its impact in creating a conducive environment in schools.